MEDIA SOSIAL SEBAGAI SARANA PUBLIC RELATIONS BISNIS DI ERA DIGITALISASI - Tengku Ine Hendriana (Journal of Business Computers, 2022)
PT. Mutiara Hikmah is an outsourcing company engaged in the field of security services and the provision of manpower, especially security personnel in the Bandung Regency area. In a business process, the use of social media as a means of Public Relations (PR) is one way to convey information both internally and externally to the company, for example employees and company relations. The social media application that is used as a company PR tool is WhatsApp by optimizing the use of existing application features. The research process was carried out by means of descriptive analysis. By using data collection techniques, namely field observations, documentary studies, literature studies and interview studies. The research results obtained are the use of WhatsApp social media can help the company's business processes improve. And based on the analysis, it is proposed to increase the use of social media as a PR tool, namely the use of the Instagram application which can make the delivery of information more effective and efficient, so that the scope of recipients of information will be even wider.